Cognitive function of children with biliary atresia after primary living donor liver transplantation - Tingge Wang; Yan Hu; Zhanzhan Zhang; Xiaoke Dai; Mingman Zhang; Yan He; Yingcun Li (BMC Pediatrics, 2024)
Abstract Background The survival rate of children with biliary atresia (BA) after liver transplantation (LT) is significantly improved, and their quality of life has attracted much attention.This study aimed to investigate the cognition and its influencing factors in children with BA after primary living donor LT (BA-pLDLT) during infancy. Methods Children with BA were recruited 6 months after pLDLT at Children’s Hospital of Chongqing Medical University (2018–2022). Demographic and clinical data were collected from the health information system. Cognition was assessed using the Chinese version of the Griffiths Mental Development scale (GMDS-C). Multivariate linear regression were used to analyze the influencing factors of their cognitive function. Results In total, 57 children with BA-pLDLT, aged 5.00(3.90–9.30) months at transplantation and 25.00(14.00-60.80) months at evaluation were included. The general developmental quotient (89.02 ± 12.07) and motor, language, eye-hand coordination, performance, and practical reasoning quotients of these children were significantly lower than the normative mean values of GMDS-C(P < 0.05). Of the 57 children, 16 (28.07%) had borderline developmental delay (DQ between 70 and 84), 3 (5.26%) had developmental delay (DQ < 70), and 11(19.29%) had language delay. Reoperation for biliary or vascular complications after pLDLT was a risk factor for decreased general development quotient and motor quotient and lower ZW at assessment was associated with decline motor quotient. Conclusion Children with BA-pLDLT have varying degrees of developmental delays in early life. Reoperation and nutritional deficiencies had adverse effects on cognitive development.